Therapeutic Potency of Mangosteen (Garcinia mangostana) Peel Extract For Shigella dysenteriae Infected Mice’s Colon Mucosal Destruction - Achmad Ilham Rizwani; Arifa Mustika; Lindawati Alimsardjono (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction : Antibiotics treatment for bacillary dysentery due to Shigella dysenteriae infection have shown resistancy. Mangosteen (Garcinia maangostana) peel have a therapy potency for Shigella dysenteriae infection due to its antibacterial and antiinflamation activity.Methods : This research was an experimental research, 30 mice was used which divided to 5 groups. The mice was infected with Shigella dysenteriae intraperitoneally, then azithromycin, aquadest, and 3 different doses of mangosteen (Garcinia mangostana) peel was given for each group for 5 days, which then the mice’s colon was collected and made into histopathology slide and its mucosal destruction was observed in 3 fields of view in each slide, 1 – 4 score was given acording to its mucosal destruction. Kruskal-Wallis test is used to analyze the data and then Mann Whitney test also used for further analysis.Result : there was a healing effect obeserved when mangosteen (Garcinia mangostana) peel extract was given to the mice’s colon mucosal, 100 mg/Kg body mass dose of mangosteen (Garcinia mangostana) peel extract already given a positive effect on mice’s mucosal colon histopathological appearance, no difference observed between 3 dose given.Conclusion : Mangosteen (Garcinia mangostana) peel extract consumption gave healing appearance to destruction of colon mucosal wall of mice with Shigella dysenteriae infection at 100 mg/Kg body mass.